2014
DOI: 10.1021/jz5019256
|View full text |Cite
|
Sign up to set email alerts
|

Resonantly Enhanced Multiphoton Ionization Spectrum of the Neutral Green Fluorescent Protein Chromophore

Abstract: The photophysics of the green fluorescent protein is governed by the electronic structure of the chromophore at the heart of its β-barrel protein structure. We present the first two-color, resonance-enhanced, multiphoton ionization spectrum of the isolated neutral chromophore in vacuo with supporting electronic structure calculations. We find the absorption maximum to be 3.65 ± 0.05 eV (340 ± 5 nm), which is blue-shifted by 0.5 eV (55 nm) from the absorption maximum of the protein in its neutral form. Our resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 51 publications
(76 reference statements)
7
25
0
Order By: Relevance
“…Our calculated absorption values are 3.69 and 3.61 eV for the cis and trans conformers, respectively, and seem to confirm to be within these measurements. Our numbers are also in line with previously calculated values of 3.71 eV (CAM‐B3LYP) and 3.58 eV (CASPT2) for the cis conformer of HBDI.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Our calculated absorption values are 3.69 and 3.61 eV for the cis and trans conformers, respectively, and seem to confirm to be within these measurements. Our numbers are also in line with previously calculated values of 3.71 eV (CAM‐B3LYP) and 3.58 eV (CASPT2) for the cis conformer of HBDI.…”
Section: Resultssupporting
confidence: 92%
“…The experiment using the charge group by Rajput et al proposed the absorption at 3.35 eV . Recently, Greenwood et al applied an alternative approach and reported the absorption value to be 3.65 eV. Our calculated absorption values are 3.69 and 3.61 eV for the cis and trans conformers, respectively, and seem to confirm to be within these measurements.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Knowing that the environment of the chromophore plays a pivotal role in determining the spectral properties of GFP, which are important for imaging applications, led to numerous investigations to determine how structural modifications to the protein, such as changing single amino acid residues, can be used to tune the absorption or fluorescence properties. 4 , 16 Recently, there has also been a great deal of interest in determining how the structure and environment of the isolated chromophore influences the absorption properties 17 , 18 and dynamics. 19 For example, variants of the isolated chromophore in which the hydroxyl group was moved from the para position to the ortho position were found to be weakly fluorescent in cyclohexane ( Φ ≈ 0.003).…”
Section: Introductionmentioning
confidence: 99%
“…The GFP and its family have a profound impact on the versatility of techniques available to cell biologists studying different diseases like cancer and other genetic defects . Thus, there is an immense interest in determining how the structure and environment of the isolated chromophore influences the absorption properties and dynamics . Complete understanding of the reaction mechanism of GFP chromophore biosynthesis and reaction pathway and identification of intermediates would be highly beneficial to chemists and biologists.…”
Section: Introductionmentioning
confidence: 99%